What is Stang’s law? - Kortlandt, Frederik (Baltistica, 2017)
Stang’s law is an ambiguous concept. On the one hand, it refers to a retraction of the stress from non-acute long vowels to the preceding syllable in Slavic. On the other hand, it refers to the development of acc.sg. Vedic dyā́m ‘sky’, gā́m ‘bull, cow’, Greek Ζῆν(α), βῶν, from *dieum, *gwoum. Stang derived the long vowel from the diphthong before the tautosyllabic nasal consonant. Alternatively, the long vowel can be attributed to monosyllabic lengthening followed by the loss of *‑u‑ before the tautosyllabic nasal.I have proposed that *‑u‑ was lost before word-final *‑m at a stage before the monosyllabic lengthening, yielding *diēm
Keywords: Balto-Slavic; Indo-European; historical phonology; Stang’s law